The greatest contribution to medical science is the transformation from studying symptoms to studying their causes—the unrelenting legacy of Robert Koch and Louis Pasteur—and a causality perspective to approach a definition of SLE - Rekvig, Ole Petter (Frontiers in Immunology, 2024)
The basic initiative related to this study is derived from the fact that systemic lupus erythematosus (SLE) is a unique and fertile system science subject. We are, however, still far from understanding its nature. It may be fair to indicate that we are spending more time and resources on studying the complexity of classified SLE than studying the validity of classification criteria. This study represents a theoretical analysis of current instinctual1 SLE classification criteria based on “the causality principle.” The discussion has its basis on the radical scientific traditions introduced by Robert Koch and Louis Pasteur. They announced significant changes in our thinking of disease etiology through the implementation of the modern version of “the causality principle.” They influenced all aspects of today’s medical concepts and research: the transformation of medical science from studies of symptoms to study their causes, relevant for monosymptomatic diseases as for syndromes. Their studies focused on bacteria as causes of infectious diseases and on how the immune system adapts to control and prevent contagious spreading. This is the most significant paradigm shift in the modern history of medicine and resulted in radical changes in our view of the immune system. They described acquired post-infection immunity and active immunization by antigen-specific vaccines. The paradigm “transformation” has a great theoretical impact also on current studies of autoimmune diseases like SLE: symptoms and their cause(s). In this study, the evolution of SLE classification and diagnostic criteria is discussed from “the causality principle” perspective, and if contemporary SLE classification criteria are as useful as believed today for SLE research. This skepticism is based on the fact that classification criteria are not selected based on cogent causal strategies. The SLE classification criteria do not harmonize with Koch’s and Pasteur’s causality principle paradigms and not with Witebsky’s Koch-derived postulates for autoimmune and infectious diseases. It is not established whether the classification criteria can separate SLE as a “one disease entity” from “SLE-like non-SLE disorders”—the latter in terms of SLE imitations. This is discussed here in terms of weight, rank, and impact of the classification criteria: Do they all originate from “one basic causal etiology”? Probably not.